PHONOLOGICAL PROCESSING OF VISUAL-SPEECH: THE PHONOLOGICAL MAPPING NEGATIVITY (PMN) AMPLITUDE IS SENSITIVE TO FEATURES OF ARTICULATION - Harrison, Angela V. (My University, 2012)
The goal of this study was to elucidate whether articulations of visual-speech are processed phonologically, and in the same manner as auditory-speech. Phonological processing, measured through the amplitude of the Phonological Mapping Negativity (PMN), was compared across three conditions using the electroencephalogram (EEG). Planned polynomial contrasts compared conditions of related and unrelated linguistic stimuli versus a non-linguistic control stimulus. A significant Site x Condition polynomial trend at posterior sites (Pz and Oz) during the N400 tine window revealed that the unrelated condition was most negative in amplitude, an N400-like deflection in the control condition reached similar negative amplitude, while the related condition was the most positive. A significant quadratic trend of PMN amplitude differentiated between the linguistic conditions and the non-linguistic control at site Fz, but did not differentiate the related and unrelated linguistic conditions from each other. These results support a conclusion that non-lexical speech-like and gurning motions of the lips are treated differently than articulations of a meaningful nature. Moreover, the PMN response patterned similarly in the linguistic conditions, compared to the non-linguistic control, indicating phonological processing. The prediction that PMN amplitude will distinguish visual-speech events congruent or incongruent to a phonologically constrained context was not supported.
Keywords: speech processing; phonological mapping negativity (PMN); electroencephalogram (EEG); phonological processing; speechreading; visual-speech; event related potentials; Cognition and Perception; Phonetics and Phonology; Psycholinguistics and Neurolinguistics; Cognition and Perception